Cultural Heritage as a Branding Strategy: How Malang’s SMEs Leverage Local Identity for Authentic Marketing - Gustiawan, Wahyu Dede; Sudarmiatin (RISK : Jurnal Riset Bisnis dan Ekonomi, 2025)
This study examines the strategy of using cultural heritage as a branding tool by MSMEs in Malang, with a focus on building brand authenticity through the integration of local identity. The qualitative method of case studies was applied to 7 MSMEs in the batik, culinary, and handicraft sectors that actively raised cultural elements such as Malangan batik motifs meaning Majapahit history, the narrative of Malang's meatball philosophy, and the cultural destination of the Jodipan Colorful Village. The findings revealed that MSMEs have succeeded in increasing the perception of brand authenticity by 35-40% through: (1) collaboration with local communities in validating historical narratives, (2) incorporation of tangible cultural symbols (product design) and intangible (folklore), and (3) limited adaptation of digital technologies such as augmented reality (AR) and micro-influencer content. However, the main challenge lies in the dichotomy between the depth of cultural narratives and the algorithmic demands of digital platforms—viral content on TikTok conveys only 12-18% of key cultural information, well below 58% of website content. This research introduces a layered storytelling model as a solution, where cultural narratives are spread in stages from concise content on social media to in-depth articles on specialized platforms. Policy implications include recommendations for Cultural Authenticity Label certification by local governments and AR/VR technology subsidy schemes for MSMEs.